2020
DOI: 10.1016/j.jaci.2019.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal mammalian target of rapamycin complex 2 controls lipid synthesis and filaggrin processing in epidermal barrier formation

Abstract: From a the Department of Dermatology, b the Center for Molecular Medicine Cologne (CMMC), and g the Cluster of Excellence Cellular Stress Responses in Aging-associated Diseases (CECAD),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…S4). Changes in the metabolites involved in the BCAA pathway are known to influence the regulation of mTOR 23,24 , which plays a vital role in epidermal barrier formation and the signaling axis for the control of filaggrin as the fundamental pathophysiology of AD [25][26][27][28] . Third, propyl-paraben exposure is associated with aeroallergen sensitization and increased EASI score via the peroxisome proliferator-activated receptors (PPAR) pathway, which is based on decreased levels of palmitic acid and 2-palmitoylglycerol found in our study 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…S4). Changes in the metabolites involved in the BCAA pathway are known to influence the regulation of mTOR 23,24 , which plays a vital role in epidermal barrier formation and the signaling axis for the control of filaggrin as the fundamental pathophysiology of AD [25][26][27][28] . Third, propyl-paraben exposure is associated with aeroallergen sensitization and increased EASI score via the peroxisome proliferator-activated receptors (PPAR) pathway, which is based on decreased levels of palmitic acid and 2-palmitoylglycerol found in our study 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated the mTOR role in epidermal stratification and cornification. Indeed, Ding and colleagues, have shown that mTORC2 controls FLG processing and de novo epidermal lipid synthesis during cornification in mice lacking RICTOR in the epidermis (113). Furthermore, increased transcriptional levels of the regulatory-associated protein of mTORC1, RAPTOR, correlate with decreased FLG expression, barrier defects and presence of inflammatory markers in skin of patients with AD (114).…”
Section: Dual Effects Of Pi3k Pathways In Inflammatory and Hyperproliferative Skin Diseasesmentioning
confidence: 99%
“…Previous studies by Ding et al 10 demonstrated that mTOR signaling is indispensable for epidermal barrier formation, 9 although with differential roles defined for mTORC1 and mTORC2. By crossing mice carrying loxP-flanked target alleles (Mtor fl/fl , Rptor fl/fl , or Rictor fl/fl ) with human keratin 14 Cre recombinase transgenic mice, Ding et al 10 were able to respectively abolish complete mTOR signaling, mTORC1 activation, or mTORC2 activation specifically in the epidermis. 9 Deletion of Mtor in mouse epidermis (mTOR EKO ) resulted in newborns with defective epidermal barrier function that succumb to death shortly after birth.…”
mentioning
confidence: 99%
“…Recent studies have revealed that mTORC1 is crucial for keratinocyte proliferation and the early epidermal differentiation program. 9 In this issue of the Journal of Allergy and Clinical Immunology, Ding et al 10 show that mTORC2 signaling controls the terminal differentiation and function of keratinocytes in the late stage of epidermal barrier formation (Fig 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation